Foreign Direct Investments Induced Innovation? A Case Study – Macedonia - Apostolov, Mico (Comparative Economic Research. Central and Eastern Europe, 2016)
This paper, while analysing innovation in Southeast Europe, and in particular the case study of Macedonia, focuses on the basic ties between foreign direct investments and innovation. Foreign direct investment is usually defined as dominant or controlling ownership of a company in one country (the host country), by an entity based in another country. The concept of industry-government-university relationships interprets the change from a dominating industry-government duo in the ‘industrial society’ to a growing triadic relationship between industry-government-university in the ‘knowledge society’. From the beginning of the transition process, foreign direct investments have been a priority, an essential pillar that moves the society forward towards a developed market economy. In addition, as the influx of capital increases it inevitably brings with it increased innovation. Hence we examine the possibility that these two indicators have a positive and upward ascent and facilitate the development of the economy.